Depression, anxiety and related factors among Syrian breast cancer patients: a cross-sectional study - Soqia, Jameel; Al-shafie, Mohammed; Agha, Laila Yakoub; Alameer, Mhd Basheer; Alhomsi, Dima; Saadoun, Rakan; Saifo, Maher (BMC psychiatry, 2022)
Breast cancer represents a traumatic experience with a psychological burden. The prevalence of psychological distress (which include depression and anxiety) among breast cancer patients is estimated to be 15 to 54%, but studies have shown that applying some psychological treatments has contributed to decreasing depression and anxiety. So, it is crucial to diagnose and treat patients with the appropriate means. After reviewing the literature, no studies discussed depression and anxiety among Syrian breast cancer patients.
Gesehen am 06.02.2023